-7(x+1)=13

Simple and best practice solution for -7(x+1)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+1)=13 equation:


Simplifying
-7(x + 1) = 13

Reorder the terms:
-7(1 + x) = 13
(1 * -7 + x * -7) = 13
(-7 + -7x) = 13

Solving
-7 + -7x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -7x = 13 + 7

Combine like terms: -7 + 7 = 0
0 + -7x = 13 + 7
-7x = 13 + 7

Combine like terms: 13 + 7 = 20
-7x = 20

Divide each side by '-7'.
x = -2.857142857

Simplifying
x = -2.857142857

See similar equations:

| y-4=4*(1+0) | | -2(x-4)=3x+6-1x | | 12=a/5-4 | | 13(x-1)=7x+23 | | 15x=18+13x | | 13y+36=153 | | 8(4s+9)=328 | | -3x-6/4=3 | | y^2-xy-3x=1 | | 1/6x-9=-2 | | 2x-21=5x-3y-12 | | (2x-7)+(3x+4)=0 | | 10x^4=0.001 | | (7/4)(-5) | | 15p+p+-19p+20p+-14p-16=-2 | | 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 | | -13h+8h+10h=-20 | | -5x+4x=-20 | | (1-2a)x^2-2ax-1=0 | | 4x^2-29+5x+1=0 | | 9(6x+2)whenx=9 | | (8+i)(7+5i)=0 | | 2*m*n*8= | | 3x+12-5x+10=2x-5x+5 | | q^2-11q+30=0 | | -10x+30=-3x+100 | | 4/x-2=43 | | x^2-8x-15=3x-3 | | x^2+10x+3=7x+1 |

Equations solver categories